THEEFFECT OF DIFFERENT COOKING PROCESS OF COMMON CARP FISH MEAT (Leptobarbus hoevenii) ON THEQUALITY OF THE FISH ABON PRODUCED - Maisaputra, Rio; ', Edison; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was aimed to determine the shelf life of common carp (Leptobarbus hoevenii) fish abon in different processing method, namely steamed and presto. The results showed that the fish abon processed by presto was more preferred by consumers compared to that by steamed. The characteristics of the appearance of the fish abon presto was colored slightly brown, the texture was fibrous rather soft, the odor was fragrant and specific fish abon, and thetaste was delicious and specific abon fish.The chemical characteristic during storagefor 30 days was containing moisture (5.63%), ash (5.58%), fat (20.61%), protein (37.55%), and calcium (3769.58 mg/100g Ca). It also contained bacteria as TPC (total plate count) (4,07 x 104 sel/gram)Keyword : common carp, steam, presto, shelf life